Implementasi Sistem Notifikasi untuk Pengawasan Pasien Alzheimer Berbasis Bluetooth Low Energy (BLE) - Aries Pratiarso; Trisna Agung Mahendra; Mike Yuliana; Prima Kristalina; I Gede Puja Astawa; Arifin Arifin (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2018)
Alzheimer's patients need attention and special treatment due to their inability to remember something. One technology that is widely used for tracking objects or people in an indoor environment is a Bluetooth Low Energy (BLE). In this paper, a surveillance notification system for Alzheimer's patients is proposed using Beacon technology to prevent the lossof patients. Improvement in accuracy of the estimated position of the patient were calculated using a Kalman filter. The reason for using this method was the difficulty of determining the location of objects due to noise and inaccuracy of measurement data.Fromthe results of the tests performed, it can be seen that the system made is able to provide notifications to nurses if the patient exceeds the specified distance with an average success of up to 90%. The use of the Kalman method is also able to increase the accuracy of the estimation of patient position with an estimated error reduction of 69.7%.